Production of bio-polyethylene/wood flour biocomposites compatible with PE-g-MA. Assessment of maleic anhydride content in mechanical and thermomechanical properties (Research, Society and Development, 2021)
The production of ecological materials is being encouraged, aiming to minimize environmental impacts and promote greater sustainability. Therefore, this work aimed to develop bio-polyethylene biocomposites (BioPE)/wood flour (WF), using polyethylene grafted with maleic anhydride (PE-g-MA) as a compatibilizer. The biocomposites were prepared in a corrotational twin screw extruder and injection molded. The properties of Izod impact strength, tensile strength, Shore D hardness, Heat Deflection Temperature (HDT) and water absorption were investigated. Impact strength improved when biocomposite BioPE/WF was made compatible with PE-g-MA. This increase was more expressive for 10% of PE-g-MA with a high degree of maleic anhydride grafting, indicating a higher level of interaction between the phases. The BioPE/WF/PE-g-MA biocomposites showed improved elastic modulus, tensile strength, Shore D and HDT hardness, compared to the non-compatible biocomposite. An important aspect was the reduction of water absorption for biocomposites compatible with PE-g-MA, suggesting a greater barrier effect for the diffusion of moisture. From the point of view of the degree of grafting of maleic anhydride in PE-g-MA, in general, impact strength was the most sensitive property. The results indicate that wood flour is a waste with the potential to be reused in the development of biocomposites.